Competency in Chest Radiography Interpretation by Junior Doctors and Final Year Medical Students at a Teaching Hospital - Bashiru Babatunde Jimah; Anthony Baffour Appiah; Benjamin Dabo Sarkodie; Dorothea Anim (Radiology Research and Practice)
Background. Chest radiography (CXR) is a widely used imaging technique for assessing various chest conditions; however, little is known on the medical doctors’ and medical students’ level of skills to interpret the CXRs. This study assessed the residents, medical officers, house officers, and final year medical students’ competency in CXRs interpretation and how the patient’s clinical history influences the interpretation. Methods. We conducted a cross-sectional study in the Cape Coast Teaching Hospital in the Central Region of Ghana among 99 nonradiologists, comprising 10 doctors in residency programmes, 18 medical officers, 33 house officers, and 38 final year medical students. The data collection was done with a semistructured questionnaire in two phases. In phase 1, ten CXRs were presented without patient’s clinical history. Phase 2 involved the same ten CXRs presented in the same order alongside the patient’s clinical history. Participants were given 3 minutes to interpret each image. Median and interquartile ranges were used to describe continuous variables, while frequencies and percentages were used to describe categorical variables. Test of significant difference and association was conducted using a Wilcoxon rank-sum test/Kruskal–Wallis test and chi-square (X2) test, respectively. Results. The average score for interpreting CXRs was 7.0 (IQR = 5–8) and 4.0 (IQR = 3-4), when CXRs were, respectively, presented with and without clinical history. No significant difference was seen in average scores regarding the levels of formal training. Without clinical history, only 40.0% of residents, 22.2% of medical officers, 24.2% of house officers, and 13.2% of medical students correctly interpreted CXRs, while more than 75% each of all categories correctly interpreted CXRs when presented with clinical history. However, all participants had difficulties in identifying CXR with pneumothorax (27.3% vs. 30.3%), pneumomediastinum or left rib fracture (8.1% vs. 33.3%), and lung collapse (37.4% vs. 37.4%) in both situations, with and without patient clinical history. Conclusion. The patient’s clinical history was found to greatly influence doctors’ competence in interpreting CXRs. We found a gap in doctors’ and medical students’ ability to interpret CXRs; hence, the development of this skill should be improved at all levels of medical training.